 # I want to derive Gauss's law for magnetism, <mi mathvariant="normal">&#x2207;<!-- ∇ --> &#x Jamison Rios 2022-07-15 Answered
I want to derive Gauss's law for magnetism,
$\mathrm{\nabla }\cdot \stackrel{\to }{B}=0\phantom{\rule{thinmathspace}{0ex}}.$
The derivation in Griffiths Introduction to elecrodynamics uses

but to use this, I would need $\stackrel{\to }{J}×\frac{\stackrel{\to }{r}}{{r}^{3}}$ and $\mathrm{\nabla }\cdot \left(\stackrel{\to }{J}×\frac{\stackrel{\to }{r}}{{r}^{3}}\right)$ to be continuous.
Since $\stackrel{\to }{J}=\rho \stackrel{\to }{v}$ , then if $\rho$ (charge density) has a continuous derivative, I'm done; but, I'm not sure why can I affirm this because clearly, I can construct charge distributions with jump discontinuities.
You can still ask an expert for help

• Live experts 24/7
• Questions are typically answered in as fast as 30 minutes
• Personalized clear answers

Solve your problem for the price of one coffee

• Math expert for every subject
• Pay only if we can solve it Jordan Mcpherson
I don't believe continuity is required. So long as the only source is some current $\stackrel{\to }{J}$ and not some monopole, you should be able to prove $\mathrm{\nabla }\cdot \stackrel{\to }{B}=0$
You'll notice in Griffiths when he presents the expression:

It's allowable to move the gradient operator inside the integral regardless of the current density because the bounds are fixed space (i.e. constants that are not functions of $\stackrel{\to }{r}$ ). This means we fall into the special case of the Leibniz integral rule where the gradient operator and the integral signs are interchangeable.
His argument that the RHS is zero comes from the following vector identities:
$\mathrm{\nabla }\cdot \left(\stackrel{\to }{J}×\frac{\stackrel{\to }{r}}{{r}^{3}}\right)=\frac{\stackrel{\to }{r}}{{r}^{3}}\cdot \left(\mathrm{\nabla }×\stackrel{\to }{J}\right)-\stackrel{\to }{J}\cdot \left(\mathrm{\nabla }×\frac{\stackrel{\to }{r}}{{r}^{3}}\right)$
Because $\stackrel{\to }{J}$ is dependent on the source space (x′,y′,z′) and not the measurement space where we are taking the curl (x,y,z), we can say the curl of the current density is zero. Now we need only to evaluate the second term, which we can expand using another product rule.
$\mathrm{\nabla }×\frac{\stackrel{\to }{r}}{{r}^{3}}=\frac{1}{{r}^{3}}\left(\mathrm{\nabla }×\stackrel{\to }{r}\right)-\stackrel{\to }{r}×\left(\mathrm{\nabla }\frac{1}{{r}^{3}}\right)$
Both of these terms go to zero because the curl of $\stackrel{\to }{r}$ is zero, and because $\stackrel{\to }{r}×\stackrel{\to }{r}$ is zero (I'm not sure exactly why Griffiths makes this last step, I would have believed that $\mathrm{\nabla }×\frac{\stackrel{\to }{r}}{{r}^{3}}=0$ from the same argument).
Regardless, the result does not depend on the continuity of the current density, just the space in which the problem is defined.

We have step-by-step solutions for your answer!